University of Patras: A "Green" University? A Case Study of a Greek University Institution - Kavasakalis, Aggelos; Sidiropoulou, Kyriaki (Advances in Social Sciences Research Journal, 2023)
The unprecedented intensity of climate change shows how urgent the need to make our societies more sustainable is. It is therefore positive that many enterprises and educational organizations worldwide are making efforts to integrate the principles of sustainable development into their way of operating. The aim of this article is to highlight the research findings on the actions and processes adopted in a Greek university, the University of Patras, to promote sustainability and ‘green’ operation. It is a qualitative survey conducted at the University of Patras with the participation of 13 professors of the university as the key - actors as they: a) teach relevant courses, b) participate in relevant actions, c) hold (at the time of the research) positions of responsibility in the leadership of the university. By generating the data, through the use of thematic analysis of official university texts and semi-structured interviews it is concluded that this university is in an early stage of transformation to a green operating model.